Primary Cardiac Burkitt Lymphoma Presenting with Abdominal Pain - Tzachanis, Dimitrios; Dewar, Rajan; Luptakova, Katarina; Chang, James D.; Joyce, Robin M. (Case Reports in Hematology, 2014)
We describe the case of a 44-year-old woman with primary Burkitt lymphoma of the heart who presented with abdominal bloating and epigastric discomfort secondary to tamponade physiology caused by a large pericardial effusion. The pericardial fluid contained a large number of highly atypical lymphocytes with moderate basophilic cytoplasm, rare punched-out vacuoles, a vesicular nuclear chromatin, large nucleolus, and marginated chromatin that by FISH were positive for the 8;14 translocation. She had no other sites of disease. She was treated with four alternating cycles of modified CODOX-M and IVAC in combination with rituximab and remains in remission more than 5 years since diagnosis.